ROBO1 p.E280* Loses the Inhibitory Effects on the Proliferation and Angiogenesis of Wild-Type ROBO1 in Cholangiocarcinoma by Interrupting SLIT2 Signal - Zhou, Tao; Zhang, Yaodong; Chen, Yananlan; Shan, Jijun; Wang, Jifei; Wang, Yirui; Chang, Jiang; Jiang, Wangjie; Chen, Ruixiang; Wang, Ziyi; Shi, Xiaoli; Yu, Yue; et al. (Frontiers in Oncology, 2022)
Background: Cholangiocarcinoma (CCA) remains one of the most lethal malignancies with an increasing incidence globally. Through whole-exome sequencing of 67 CCA tissues, we identified new mutated genes in CCA, including MACF1, METTL14, ROBO1 and so on. The study was designed to explore the effects and mechanism of ROBO1 wild-type (ROBO1WT) and ROBO1E280* mutation on the progression of CCA. Methods: Whole-exome sequencing (WES) was performed to identify novel mutations in CCAs. In vitro and in vivo experiments were used to examine the function and mechanism of ROBO1WT and ROBO1E280* in cholangiocarcinoma. A tissue microarray including 190 CCA patients and subsequent analyses were performed to indicate the clinical significance of ROBO1. Results: Through whole-exome sequencing, we identified a novel CCA-related mutation ROBO1E280*. ROBO1 was downregulated in CCA tissues and the downregulation of ROBO1 was significantly correlated with poor prognosis. ROBO1WT suppressed the proliferation and angiogenesis of CCA in vitro and in vivo while ROBO1E280* lost the inhibitory effects. Mechanically, ROBO1E280* translocated from the cytomembrane to the cytoplasm and interrupted the interaction between SLIT2 and ROBO1. We identified OLFML3 as a potential target of ROBO1 by conducting RNA-Seq assays. OLFML3 expression was downregulated by ROBO1WT and recovered by ROBO1E280*. Functionally, the silence of OLFML3 inhibited CCA proliferation and angiogenesis and was sufficient to repress the loss-of-function role of ROBO1E280*. Conclusions: These results suggest that ROBO1 may act as a tumor suppressor and potential prognostic marker for CCA. ROBO1E280* mutation is a loss-of-function mutation and it might serve as a candidate therapeutic target for CCA patients.